THE EFFECT OF INFLUENCER IMITATION ON PURCHASE INTENTION MEDIATED BY SOCIAL COMPARISON AND FOMO AT FINE DINING RESTAURANTS IN JAKARTA - Yenita , Yenita; Cintalia, Meivina (International Journal of Application on Economics and Business, 2023)
This study aims to examine and analyse the effect of influencers imitation on purchase intention mediated by social comparison and FoMO at fine dining restaurant in Jakarta. This research uses a quantitative descriptive research approach with a total of 150 respondents. The data analysis technique used is Partial Least Squares through Structural Equation Modeling. The results in this study show that there is a positive and significant relationship between the act of imitating influencers with social comparison and materialism. In addition, the influence of social comparison and FoMO can mediate the relationship between imitating influencers and purchase intention. This research aims to be able to contribute to the fine dining restaurant business, especially in utilising the psychological tendency to imitate influencers in society.